Tumanyan’s Portrait According to Paruyr Sevak - Kalantaryan, Zhenya (Bulletin of Yerevan University B: Philology, 2025)
The article highlights the perceptions and criteria by which the author, Sevak, is guided in his study as a literary scholar. Special attention is drawn to Sevak’s analytical method, in which he first identifies the central directions and thematic preferences in Tumanyan’s work. These themes take on a generalizing and, to some extent, symbolic meaning. Sevak’s analysis does not follow the widely accepted chronological principle; instead, he presents the generalizing and symbolic titles in Tumanyan’s work in a sequential manner along what can be seen as a horizontal line. These titles are "Sigh," "With My Homeland," and "Toward the Infinite." Under these headings, Sevak reveals Tumanyan’s philosophy of life. Based on these generalizations, the article draws attention to the evaluations Sevak gives of Tumanyan. It also uncovers the principles of Sevak’s approach: comparing Tumanyan with other great figures of Armenian culture, particularly literary giants like Khorenatsi, Narekatsi, and Abovyan. Thus, the article has two layers: Sevak’s approach to placing Tumanyan among the greats, and Sevak’s characterization as a literary scholar based on the principles mentioned above.